The effect of the microelement preparation on the morphobiochemical composition of the blood of calves - S. V. Nikolaev (Аграрная наука Евро-Северо-Востока, 2021)
The paper presents an assessment of the effect of the Sedimine microelement product on the morphobiochemical composition of the blood of calves during the milk feeding period. For the experiment, 2 groups of heifers of HolsteinKholmogory breed at the age of 2-3 weeks were formed. The calves of the experimental group were injected intramuscularly with Sedimine at a dose of 5 ml three times with an interval of 7 days, and the control animals were given a saline solution in the same way. Blood for hematological and biochemical studies was obtained at the beginning of the experiment and a week after the first and last injection. According to the research it has been established, that after a single injection of Sedimine, there were no evident changes in the biochemical profile of the blood, with the exception of a decrease in the level of urea by 30.6% (from 4.9 to 3.4 mmol/l; P<0.001). After three-time administration of the drug, there was an increase in total protein by 9.6 % (from 54.2 to 59.4 g / l; P<0.05) and an increase in AlAT activity by 1.2 times (P<0.001), while in comparison with the control, the activity of AsAT was greater (P<0.01) by 43.4 % (57.5 U/l). The de Ritis coefficient in the experimental group decreased by 43.1 % (to 6.2; P<0.01), while in the control group, on the contrary, the indicator increased by 32.1 % (to 11.1). The ratio of calcium to phosphorus in all animals decreased by 28.8...32.1 % (P<0.001), but in young animals treated with Sedimine, the ratio was 16.7 % (0.84) higher compared to the intact group of calves (P<0.05). The concentration of thyroglobulin in the experimental group significantly decreased by 29.4 % (from 0.34 to 0.24; P<0.01), with stable values in calves that were treated with saline. Injections of the preparation contributed to the stable maintenance of iron in the blood of animals of the experimental group, the concentration of which was 3 times higher (P<0.01) in relation to the control, where the indicator was 5.9 micromol/l. Also, the control animals showed a decrease in the number of red blood cells by 31.9% (from 4.7 * 10 12 to 3.2*10 12) and hemoglobin by 19.5% (from 87.2 to 70.2 g / l; P<0.05), with stable values in the experimental group, which were higher by 56.3 % (5.0*1012) and 22.2 % (90.2 g/l) compared to the control (P<0.05). Changes in white blood were characterized by a higher level of white blood cells in calves of the experimental group (by 27.7 %), primarily due to a 36.7 % (4.1*109 ; Р<0.01) higher number of lymphocytic cells. Thus, a three-time injection of the test drug was quite effective in preventing iron deficiency in calves during milk feeding and had a positive effect on metabolic processes.